Pengaruh Kombinasi Media Tanam dan Pemupukan terhadap Pertumbuhan Biji Tumbuhan Sarang Semut (Myrmecodia tuberosa Jack.) - Sari, Yanti Puspita; Susanto, Dwi; Hutauruk, Eva Agustriani (Al-Kauniyah: Jurnal Biologi, 2013)
Anthill plant (Myrmecodia tuberosa Jack.) or sarang semut is a native plant epiphytes from Indonesia. Anthill plants used as a medicinal because contains compounds active such as flavonoids, tannins and polyphenols that are beneficial to the human body. The aims of study to determine the influence of the media type of planting and the best of fertilization on the growth of anthill plants. This study consisted of two treatment are the first treatment plant seed germination anthill on different media of treatments that husk fuel, cocopeat, fern roots and moss. The second treatment is growth plant of anthill are using completely randomized design (CRD) with two factors different. The first factor is the growing media with 4 levels of fuel treatments, husk fuel, cocopeat, fern roots and moss. The second factor is a fertilizer with a second level of treatment that is with and without fertilizer (Gandasil D 2 g/L). Influence significantly of treatment we used Duncan test (DMRT) level of 95%. The results of study in the first treatment, anthill plant can germinate 100% in all treatment media. In the second treatment, the use of growing media and fertilizer significantly influenced the increase of plant height, leaf number and leaf area. The average of plant height in moss media with the addition of fertilizer of 35.75 mm, the highest number of leaves from all treatment media with the addition of fertilizer of 2,00 strands, the largest leaf area from cocopeat media with the addition of fertilizer of 77,02 mm2, and the increase of tubers diameter found in cocopeat media with the addition of fertilizer of 4.13 mm.